Pixie hollow games - Liu, Lucy, 1968-; Raven, 1985-; Whitman, Mae, 1988-; Song, Brenda, 1988-; Hilty, Megan; Walt Disney Studios Home Entertainment (Firm) (Burbank, Calif. : Walt Disney Studios Home Entertainment, 2013)
Join Tinker Bell and her fairy friends as they compete in Disney's animated adventure, Pixie Hollow Games. Rosetta and new arrival Chloe band together to try to break the garden fairies' legendary losing streak in this sports spectacle filled with pixie pageantry, fantastic fairy events and hilarious surprises. Clank and Bobble call the action as Rosetta and Chloe face off against the storm fairies, Rumble and Glimmer, who are vying for their fifth championship ring.
Originally broadcast in 2011.
Voices: Lucy Liu, Raven Symone, Mae Whitman, Brenda Song, Megan Hilty.
Television rating: TVG.
DVD, NTSC, dual-layer, region 1, AC-3, widescreen (1.78:1), Dolby digital 5.1.
English dialogue; English subtitles ; closed-captioned.
Keywords: Tinker Bell (Fictitious character) -- Juvenile films; Fairies -- Juvenile films; Pixies -- Juvenile films; Television programs for the hearing impaired; Children's television programs; Animated television programs; Fiction television programs